Potential antiproliferative properties of methanol and water extracts of pyrrosia piloselloides on human cervical carcinoma cell lines, HeLa - Zakaria, Fashihah (Universiti Sains Malaysia, 2016)
Cervical cancer is the third most commonly diagnosed cancer and the fourth leading cause of cancer death in female worldwide. Current estimates indicate that annually 2145 women are diagnosed with cervical cancer and 621 died from the disease. At present, the standard treatment for cervical carcinoma involves surgery, chemotherapy and radiotherapy. Combined chemotherapy using Cisplatin appears to be effective as its ability to initiate the apoptotic pathway. However, the use of Cisplatin is limited by its toxicity and acquired chemoresistance throughout the treatment. In this study, we investigated the potential antiproliferative effects of methanol and water extracts of Pyrrosia piloselloides on HeLa cell lines. MTT assay was performed to determine the IC5o concentration, whereby apoptosis analysis was done by flow cytometry to study the ability of the plant extracts to induce apoptosis in the cell lines. P. piloselloides methanol extracts (PPME) showed antiproliferative effect on HeLa cell lines with IC50 of 16.25pg/ml while P. piloselloides water extract (PPWE) showed no IC50 value. However, both extracts showed no significant effect in apoptosis assessment. Identification of the chemical compounds exist in the extract was analysed by Gas Chromatography-Mass Spectrometry (GC-MS). Major compounds exist in PPME were 5-Hydroxymethylfurfural (23.13%), Allopurinol (8.66%) and 3,5-dihydroxy-6-methyl- 2,3-dihydropyran-4-one (7.41%) while PPWE were Sulfolan-3-ol (10.06%), Linoleic acid (9.06%) and 0-Sitosterol acetate (7.98%). Further study needs to be done to investigate the reason and mechanism of anti-proliferative effect of methanol extract on HeLa cell lines.